Human rights in child protection : implications for professional practice and policy - Falch-Eriksen, Asgeir, 1976-; Backe-Hansen, Elisabeth (Online access: OAPEN DOAB Directory of Open Access Books., 2018)
This open access book critically explores what child protection policy and professional practice would mean if practice was grounded in human rights standards. This book inspires a new direction in child protection research - one that critically assesses child protection policy and professional practice with regard to human rights in general, and the rights of the child in particular. Each chapter author seeks to approach the rights of the child from their own academic field of interest and through a comparative lens, making the research relevant across nation-state practices. The book is split into five parts to focus on the most important aspects of child protection. The first part explains the origins, aim, and scope of the book; the second part explores aspects of professionalism and organization through law and policy; and the third part discusses several key issues in child protection and professional practice in depth. The fourth part discusses selected areas of importance to child protection practices (low-impact in-house measures, public care in residential care and foster care respectively) and the fifth part provides an analytical summary of the book. Overall, it contributes to the present need for a more comprehensive academic debate regarding the rights of the child, and the supranational perspective this brings to child protection policy and practice across and within nation-states.